Teaching the Use of ad hoc Corpora in the Translation of Legal Texts into the Second Language - Vigier Moreno, Francisco J. (Language and Law / Linguagem e Direito, 2016)
Translating legal texts is usually perceived as being daunting by Translation students, who normally lack legal training, and it becomes even more intimidating when legal texts must be rendered in the second language. However, translator trainees must be equipped with the skills required to successfully translate legal texts into their second language and subsequently meet this real market demand. Most legal translator training programmes seem to particularly focus on the development of thematic competence, with Law-related elements playing an outsized role and other abilities, such as technological competence, being downplayed. In this article, it is our purpose to highlight how ad hoc monolingual corpora can be useful for those who engage in the translation of specialised, legal texts into their second language, especially as corpora help retrieve phraseological and discursive information on which to base translation decisions in a more informed manner.